Epidemiology of tuberculosis in humans in Narok district with special interest on Mycobacterium bovis. - Koech, R.K. (University of Nairobi, 2001)
Bovine Tuberculosis (BTB) is an important zoonotic disease among most pastoralist communities in sub-Saharan Africa. A possible reason for this is the close association pastoralists have with livestock and their habit of consuming raw milk. The main objective of this study was to estimate the proportional morbidity of zoonotic BTB caused by M. bovis from clinical human tuberculosis (TB) cases and to identify the risk factors associated with both M. bovis and M. tuberculosis infections in Narok District, Kenya, with a focus on the role of raw milk consumption as a risk factor. The study first describes morbidity patterns from past medical records on human pulmonary tuberculosis (PTB) and extra-pulmonary tuberculosis (EXPTB) cases across the country (EXPTB cases are usually more likely to be associated with BTB that other tuberculoses). Secondly, past morbidity data from hospital records in Narok District covering both forms of TB were analysed in more detail. Thirdly, a survey questionnaire was administered to suspect TB patients reporting to 17 health units in Narok District. The questionnaire was designed to gather information on risk factors for cattle-to-human transmission of BTB. In addition, sputum and/or cervical lymph node aspirate samples from the suspect patients were obtained for laboratory identification by acid-fast staining (AFS), culture and biochemical tests to isolate the Mycobacteriacae. Available hospital records showed that approximately 180,000 TB patients were diagnosed by AFS nationally between 1990 and 1999. The national overall ratio of human PTB to EXPTB for the decade was 4:1. There was a general increase in reported cases of both forms of TB over the period (with a more marked increase between 1996 and 1999), the general rate of which cannot be explained by population growth or increase in number of hospital visits alone: EXPTB cases increased by 26% annually, significantly higher than the rate of increase of PTB cases (17%). EXPTB occurrence nationally was uncorrelated with production system or population densities of either cattle or humans. There were about 120,000 outpatient-visits in Narok District in 1999, similar to the figures of the previous nine years. In the same year, clinical diagnoses of human TB in the district were 2,603. Of these, 225 (9%) were confirmed as being acid-fast positive (AFB+), indicating the presence of tubercle bacilli. Most (83%) of the AFB+ patients had pulmonary symptoms. The rest (17%) of the patients presented extra-pulmonary symptoms with or without pulmonary symptoms. A total of 159 patients (135 from the lowland extensive pastoral area and 24 from the highland sedentary area) were clinically diagnosed and sampled for TB during the nine-month period of study from April to December 2000 in Narok District. Of these, 132 (83%) were positive on acid-fast bacilli testing. On culture, only 32 (24%) out of the 132 samples yielded Mycobacterium tuberculosis. No Mycobacterium bovis was isolated. The sampling accuracy implies that one can be 95% confident that TB cases in the district that are bovine are not more than 2%. The rest 100 AFB+ cases (76% of the 132 tubercle bacilli positive samples) were not speciated. These likely represented atypical and non-pathogenic tubercle bacilli that were neither M. tuberculosis nor M. bovis. Descriptive results showed that most households (hhs) that kept cattle also consumed raw blood and raw beef (p < 0.01). Most patients (68%) sought health services in private/mission health units compared to Government health facilities. Coughing was the best predictor of TB infection with 75% sensitivity, 67% specificity and positive predictive value of (PV+ve) of 92% for AFB+ result. Significantly more samples from patients living in the lowland pastoral areas were AFB+ (91%) compared to samples from patients living in the highland areas (38%). Consumption of raw milk by 33% of patients was protective for human TB (p < 0.01), but consumption of other raw animal products (blood or beef) was not (p > 0.1). Marital status, age, sex, previous exposure to same infection as clinically perceived by the patient and family size were not associated with TB infection (p > 0.1). The study concludes that though these findings vindicate the long held official position indicating absence of bovine tuberculosis in Kenya, the findings need to be verified in other areas and periodically, given the risk posed by frequent movement of pastoral livestock across borders from neighbouring countries. If M. bovis were present in Kenya, those at the greatest risk of acquiring BTB would be those pastoralists who consume raw milk and/or other raw animal products. It appears from this study that raw milk consumption and possible ingestion of atypical non-pathogenic Mycobacteriaceae that may be present in raw milk offers some protective immunity against M. tuberculosis infection. However, this benefit, if true, is likely to be outweighed by the risk of infection from other pathogens such as brucellae that can be potentially transmitted through consumption of raw milk. Boiling of raw milk is therefore advised before it is consumed.